Comparative Evaluation of Feature-Driven Development and Scrum in Public Facility Booking Systems - Wahdini Wahdini; Hilyah Magdalena (Politeknik Ganesha Medan, 2026)
The Parittiga Sub-District Office still relies on manual procedures for multipurpose building borrowing, resulting in limited schedule transparency, double booking vulnerabilities, and delayed confirmations. However, a critical research gap exists: no quantitative comparison between Feature-Driven Development (FDD) and Scrum has been conducted for public facility booking systems. To address this, a web-based booking system was developed using FDD and empirically compared with Scrum through a comparative experimental design. Using identical two-developer teams, both methods were evaluated across five metrics: development time per feature, functional error rate (black-box testing), developer understanding (1-5 scale), usability (SUS), and end-to-end borrowing efficiency. Findings demonstrate that FDD outperforms Scrum with 50% fewer functional errors (2 vs 4), higher developer understanding (4.3 vs 3.8), and better usability (84.2 - Excellent vs 71.6 - Good), despite requiring 2 additional hours per feature (12 vs 10). Moreover, the FDD-based system accelerates the complete borrowing process by 63% (4 vs 11 minutes). This research contributes empirical evidence to the agile methodology literature and offers a structured, replicable evaluation framework for practitioners selecting development methods for stable, documentation-intensive public service environments.